Omphaloplasty: Y/V technique - Vitor Hugo Moreira Guimarães; Victor Antunes Guimarães; Fernando de Azevedo Gonçalves; Paulo César Caires de Carvalho (Revista Brasileira de Cirurgia Plástica)
Introduction: Omphaloplasty is a crucial procedure during abdominoplasty surgery. Although it is currently considered an important step, omphaloplasty was not always performed during abdominoplasties, and the umbilicus was sometimes discarded together with the fat flap. Various techniques were used to preserve the umbilicus and underwent modifications with time to allow for an increasingly natural result. Method: The proposed "Y"/"V" technique consists of modeling the umbilical stump to perfectly fit in the same place where the umbilicus was located. The umbilical island, after being modeled, is sutured, resulting in a "Y"/ "V" image, which gives rise to the name. Results: A low number of complications (11.34%) were observed when analyzing the postoperative follow-up data. Suture dehiscence, umbilical stenosis, color alterations in the scar, and keloid scars were the complications observed, which were surgically corrected six months postoperatively. Conclusion: The proposed technique is simple to implement, with low rates of complications and results in a more natural aspect of the neoumbilicus scar. Further studies are required to prove its effectiveness in comparison to the other techniques that are currently in use.